Menimbang Gagasan Farid Esack Tentang Solidaritas Lintas Agama - Umam, Fawaizul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
Inter-religious conflict has been part of the history of religions. To the dismay of many, the conflict has escalated from time to time overshadowing the benevolent nature of religions as a blessing for mankind. Hence, instead of addressing the formidable problems of poverty, backwardness, ignorance, injustice, oppression and the like, people of different religions in one way or another are dragged into the acts of violence. It is this unfortunate development in the history of religions that we are interested in discussing by appealing to the ideas of Farid Esack who has established himself as an international scholar of Islam. We portray Esack as a man whose attention is being paid solely to promote the inter-religious dialogue with a single purpose in mind, to push peace and harmony for all regardless of their race and religion. We are particularly interested in developing further the idea of what he calls a âproductive dialogueâ in which an awareness of religious solidarity constitutes an integral part. We will try to expose the âhermeneutics of awarenessâ to get a better idea of what Esack is trying to do as far as social harmony is concerned. Within this scheme we will also discuss some other related issues such as the problem of pluralism and liberation. We argue that Esack sees the problem of social harmony as essentially theological and not simply political. It is therefore the task of religionâand not simply of politicâto deal with such problem.